SAT0084 Evaluation of Functional Disability in Patients with Clinically Suspect Arthralgia. (15th July 2016) - Ten Brinck, R.M.; van Steenbergen, H.W.; Mangnus, L.; Burgers, L.E.; Reijnierse, M.; Huizinga, T.W.J.; Van der Helm–van Mil, A.H.M.
Abstract : Background: A phase of arthralgia precedes the emergence of rheumatoid arthritis (RA). This phase is not yet well characterized. The presence of MRI-detected subclinical inflammation has been identified in this phase and is correlated with RA development. However, it is unknown if patients with arthralgia at risk for RA (with and without subclinical inflammation) have functional limitations. Objectives: This study assessed functional disability in patients with clinically suspect arthralgia (CSA) and the associations with MRI-detected inflammation and progression to clinical arthritis. Methods: Between April 2012 and April 2015 patients were included in the CSA cohort. Patients with CSA were defined as having no clinical arthritis, with symptoms of hands or feet for <1 year and were considered to be at risk for RA by their rheumatologists based on their clinical presentation. At baseline, functional disability was assessed using HAQ scores and unilateral 1.5 T extremity MRIs of wrist, MCP and MTP joints were made. MRIs were scored on synovitis, tenosynovitis and bone marrow edema (BME) by two independent readers. The sum of these features yielded the total MRI-inflammation score. Pearson correlation coefficients, linear regression models, paired t-tests and Cox proportional hazards regression analyses were used. Results: Of the 255 patients included, 77% were female and the mean age was 44.2 years. Median HAQ score was 0.50 at baseline and median duration of follow-up was 61 weeks. In univariable linear regression, a higher total inflammation score was significantly associated with a higher HAQ score (β=0.01, p=0.019). Of the individual types of inflammation, tenosynovitis showed the strongest correlation (β=0.04, p=0.003). When evaluating subclinical inflammation at specific hand joints in relation to HAQ-questions measuring hand function, significant correlations were observed. For instance, difficulties with opening previously opened jars was associated with MRI-inflammation score at the wrists (Pearson r=0.18, p=0.011). Patients that progressed to clinical arthritis had higher HAQ scores at presentation, than CSA-patients that did not progress (median HAQ scores 0.90 and 0.50 respectively). HAQ scores above 0.90 in particular were associated with arthritis development (HR=2.62, 95% CI: 1.06–6.47, p=0.036) as shown in the Kaplan-Meier plot (figure 1 ). An analysis of the patients that did develop arthritis revealed that median HAQ-scores were the same both at initial presentation with CSA and at conversion to clinical arthritis (median HAQ scores 0.90 and 0.68 respectively, paired t-test p-value = 0.751). Conclusions: CSA-patients already have functional limitations. The severity of functional disability is associated with the severity of local subclinical inflammation. CSA-patients that progressed to clinical arthritis had high HAQ scores at baseline and these HAQ scores did not increase when arthritis became clinically evident. Disclosure of Interest: None declared